Actividades gráfico plásticos para el desarrollo de la preescritura en estudiantes de cinco años de la institución educativa inicial 318 Gloria Chávez Culqui, San Juan 2024 - Vela Sosa, Leslie Susan (2025)
The purpose of the study was to evaluate the effect of graphic-plastic activities on the development of pre-writing in 5-year-old preschoolers at I.E. Inicial 318 Gloria Chávez Culqui, San Juan, 2024. The methodology of the study was based on a quantitative approach, using a quasi-experimental design that included the participation of two groups: an experimental and a control group. To evaluate progress in pre-writing, tests were applied both before (pretest) and after (posttest) the intervention, considering four dimensions: pre-syllabic, syllabic, syllabic-alphabetic and alphabetic writing. The sample consisted of 30 5-year-old children, equally distributed among the groups (15 per group). The findings showed that the children in the experimental group made significant progress in all the dimensions evaluated after the intervention. In particular, the analysis with Student's t-test yielded a t-value = 4.033 with a significance p = 0.001, evidencing a remarkable effect on overall pre-writing development. This finding supports the efficacy of graphic-plastic activities, which proved to be an adequate strategy to strengthen prewriting in schoolchildren of this age, promoting skills such as fine motor skills, visual-motor coordination and a better transition to alphabetic writing. These findings support the integration of these activities in early education curriculum planning.